Routine weighing to reduce excessive antenatal weight gain: a randomised controlled trial. (January 2016) - Brownfoot, FC; Davey, M‐A; Kornman, L
Abstract : Objective: To assess whether routinely weighing women at each antenatal visit leads to a difference in gestational weight gain and weight gain within the Institute of Medicine (IOM) recommendation. Design: A randomised controlled trial. Setting: Antenatal clinics in a tertiary obstetric hospital in Melbourne, Australia. Population: Healthy women were enrolled during their antenatal booking visit if they were between 18 and 45 years of age, were <21 weeks' gestation with a singleton pregnancy. Methods: The intervention was weighing at each antenatal clinic appointment followed by counselling by their treating clinician according to IOM gestational weight gain guidelines. The control group had standard antenatal care comprising recording weight at booking and then at 36 weeks. Primary analysis was by intention‐to‐treat. Outcome: The primary outcome was difference in mean weight gain between groups. An important secondary outcome was gestational weight gain within IOM recommendations. Secondary outcomes also included maternal or neonatal morbidity. Results: Seven hundred and eighty two women consented to take part and 386 were randomised to the intervention group and 396 to the control group. There was no significant difference in weight gain between the intervention group (0.54 kg/week) compared with the control group (0.53 kg/week) ( P = 0.63). A similar proportion of women gained more weight than the IOM recommended range: 75% in the intervention group and 71% in the control group ( P = 0.21). There were no significant differences in secondary outcomes between the two groups. Conclusion: We found no evidence that regular weighing in antenatal clinics changed weight gain or was effective at reducing excessive gestational weight gain. Tweetable abstract: Weighing at antenatal visits compared with routine care did not reduce excessive weight gain in pregnancy. Tweetable abstract: Weighing at antenatal visits compared with routine care did not reduce excessive weight gain in pregnancy.